Propagation of some phenotypes of Prunus ursina K.Y in the Western Region of Syria - Ismael, Haisam; Rajab, Mazen; Ammar, Amran; Sabbouh, Safaa (Latakia University Journal -Biological Sciences Series, 2018)
This study was carried out during 2013-2014-2016, six natural distribution sites were determined (Duerbsndiana-Alnabeen-Alshohtte-Helata-Btmazah-Wadeheleen), and 35 trees were determined as samples to comparing the response to sexual and vegetative propagations and determining the initial compatibility between Prunus ursina and two species of almonds (Red Heaven peach and Diamond plum) by using tongue grafting. Germination of P. ursina averaged (90-100%) with no significant differences among them. The callus of propagation by cuts was up to 100% in January and 47% in November, while it was 0% in June. Types prevailing in Dweir Bsendiana, al-Nebain, Shouh Tai and Btmaza were more significant than those of Hilata and Wadi Hileen in terms of long and width growths of shoots resulting from grafting of plum and peach. Grafting survival ranged between 0 - 100% per region. إكثار بعض الطرز المظهرية لنوع خوخ الدب Prunus ursina K.y في المنطقة الغربية من سورية نفذ البحث خلال الأعوام 2013-2014-2016، حددت ستة مواقع طبيعية لانتشار خوخ الدب (دوير بسنديانة - النبعين - الشوح طي - حيلاتا - بتمازة -وادي حيلين) )، تم دراسة (35) طرازاً من حيث مدى استجابة بعض الطرز للإكثار الجنسي (زراعة أجنة) والإكثار الخضري (العقل الساقية) بالإضافة لتحديد درجة التوافق الأولي مابين أصل خوخ الدب وصنفين من اللوزيات (دراق ريد هبفن و خوخ الجوهرة) باستخدام التطعيم بالقلم اللساني. تبين نتيجة للدراسة أن أجنة طرز خوخ الدب ذات قدرة إنبات عالية تراوحت من(90-100)%، ولم يلحظ وجود فروق معنوية في نسب إنبات الطرز المدروسة. وعند إكثار نبات خوخ الدب خضرياً بالعقل تفاوتت نسب تشكل الكالس تبعاً لأشهر الدراسة حيث بلغت أقصاها 100% في شهر كانون الثاني، وأدناها في حزيران حيث كانت 0%. تراوحت تفوقت طرز خوخ الدب المنتشرة في مواقع (دوير بسنديانة - النبعين - الشوح طي - بتمازة) معنويا على طرز (حيلاتا -وادي حيلين) من حيث النمو الطولي والعرضي للنموات الناتجة عن التطعيم بصنفين من الخوخ و الدراق و تراوحت النسبة المئوية لنجاح التطعيم ( 0-100 )% تبعا للموقع.